A case study: developing a safe space for vulnerable young people at school. Issue 2 (17th June 2019) - Ross, Helen
Abstract : At Rushton Manor School, a small independent school in the South West of England, the proportion of young people with Autistic Spectrum Condition (ASC), a form of Social, Communication and Language Need (SCLN), was substantially higher than regional averages: 15% at the school versus 5.4% in primary schools and 8.7% in secondary schools regionally (DfE, 2017). This study explores the school's response to those students' needs in the form of the Oasis Room, part of provision of a 'safe space' and supportive structures for those students during unstructured parts of the school day. It was found that the Oasis Room improved students' experiences of social interactions, reduced behavioural incidents and allowed for proactive, supportive intervention by pastoral staff, in place of reactive 'after‐the‐fact' interventions. Suggestions are made relating to provision, structures and staff development at Rushton Manor and how these may be useful in other settings.